2005
DOI: 10.1139/t04-101
|View full text |Cite
|
Sign up to set email alerts
|

Response of a residual soil slope to rainfall

Abstract: Rainfall-induced landslides are a common problem in residual soil slopes of the tropics. It is widely known that rainfall-induced slope failures are mainly caused by infiltration of rainwater; however, the response of a residual soil slope to infiltration is not fully understood. The difficulties lie in the quantification of the flux boundary condition across the slope surface with respect to infiltration and its effect on the pore-water pressure conditions in the slope. Therefore, it is important to understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(97 citation statements)
references
References 15 publications
2
78
0
9
Order By: Relevance
“…7b), suggests that the shape of the measured infiltration capacity decay curve, and particularly the i f value measured is incorrect (the i f value would be expected to be too high). Rahardjo et al (2005) note that the initial and final volumetric content near the toe of the slope always appeared to be higher than those at the crest, suggesting that some water that infiltrates near the crest of the slope may then flow downslope, parallel to the slope surface, thus resulting in higher water content and lower suction near the toe of the slope than near the crest. The same i f value was therefore adopted for both analyses.…”
Section: Infiltration Capacity Decay Curvesmentioning
confidence: 94%
See 2 more Smart Citations
“…7b), suggests that the shape of the measured infiltration capacity decay curve, and particularly the i f value measured is incorrect (the i f value would be expected to be too high). Rahardjo et al (2005) note that the initial and final volumetric content near the toe of the slope always appeared to be higher than those at the crest, suggesting that some water that infiltrates near the crest of the slope may then flow downslope, parallel to the slope surface, thus resulting in higher water content and lower suction near the toe of the slope than near the crest. The same i f value was therefore adopted for both analyses.…”
Section: Infiltration Capacity Decay Curvesmentioning
confidence: 94%
“…2 we note that the key assumptions of the Mein-Larson model are that the minimum infiltration capacity of the soil is equal to the saturated permeability and that run-off will not occur unless the rainfall intensity exceeds the saturated permeability of the soil. Rahardjo et al (2005) report measurements of the infiltration response of a residual soil slope subjected to artificial rainfall events. The instrumented slope comprised a 1.5 m deep layer of orange silty clay with a saturated permeability of 5.18 · 10 -6 m/s, overlying a 4-5 m deep layer of purple clayey silt with K s = 1.67 · 10 -7 m/s.…”
Section: Mein-larson Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…perched water table) at the soil-bedrock interface. Several researchers (McNamara et al, 2005;Rahardjo et al, 2005;D'Odorico et al, 2005) have shown that vertical flow in the unsaturated soil zone is reduced when the infiltration front meets a less permeable layer (for example, the bedrock layer). Under this condition, the infiltrating rainwater collects at the less permeable soil layer, inducing rapid increases of pore-water pressure and unsaturated hydraulic conductivity (according to the relationship between matric suction head and unsaturated hydraulic conductivity).…”
Section: The Hydrological Modelmentioning
confidence: 99%
“…Wei in a case study of the Bukit Batok landslides in Singapore found that the failure occurred after a period of heavy rainfall and there was no rainfall at the time of failure [11]. Antecedent rainfall, initial pore-water pressures prior to a signi cant rainfall event, and the magnitude of the rainfall event play a crucial role in the development of the worst pore-water pressure condition in a slope [12].…”
Section: Introductionmentioning
confidence: 99%